Θρακολογία και ζήτημα καταγωγής των Βλάχων - Αρωμούνων - Λαζάρου, Αχιλλέας Γ. (2023)
Summary: The author describes briefly the re-emergence of the Kutsovlach question and points out that its instigators accept -and indeed they project- the autochthonous origin, as well as the Thracian origin of the Vlach-Arumanians in regions where they still live. While he accepts the validity of the argument for the autochthonous origin, he refutes the claims for the descent of the Vlachs from the ancient Thracians. To support his thesis, he presents the views of eminent scholars in the field of Thracian studies, such as C. Poghir and VI. Georgiev, as well as scholars dealing with Balkan romance languages and idioms, who refute the Thracian theories of certain contemporary writers. Finally, he cites historical sources and excerpts from works by ancient writers such as Herodotus, Polybius, Strabo, Titus Lybius and others, which support and indeed ascertain the hellenic character of the lands where the autochthonous people were latinized and have survived to our days as Vlach-Arumanians.